2019
DOI: 10.1002/ame2.12074
|View full text |Cite
|
Sign up to set email alerts
|

Efficient protocols and methods for high‐throughput utilization of the Collaborative Cross mouse model for dissecting the genetic basis of complex traits

Abstract: The Collaborative Cross (CC) mouse model is a next‐generation mouse genetic reference population (GRP) designated for a high‐resolution quantitative trait loci (QTL) mapping of complex traits during health and disease. The CC lines were generated from reciprocal crosses of eight divergent mouse founder strains composed of five classical and three wild‐derived strains. Complex traits are defined to be controlled by variations within multiple genes and the gene/environment interactions. In this article, we intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The drawbacks of the BXDs are lower precision, and a decreased amount of variation in the population compared to e.g. multiparent families (such as the Collaborative Cross and the Diversity Outbred), and a consequent decrease in the total phenotypic variance [181]. We consider this an acceptable drawback, as we have shown that medically relevant phenotypes have variation in the family and it is possible to achieve subcentimorgan mapping precision using only half of the full set of strains [82].…”
Section: Integration and Translation With Other Populationsmentioning
confidence: 99%
“…The drawbacks of the BXDs are lower precision, and a decreased amount of variation in the population compared to e.g. multiparent families (such as the Collaborative Cross and the Diversity Outbred), and a consequent decrease in the total phenotypic variance [181]. We consider this an acceptable drawback, as we have shown that medically relevant phenotypes have variation in the family and it is possible to achieve subcentimorgan mapping precision using only half of the full set of strains [82].…”
Section: Integration and Translation With Other Populationsmentioning
confidence: 99%
“… 5 The GD mice have a clear genetic background and are more genetically diverse than the commonly used inbred mice. Extensive research has been conducted on complex trait regulation and disease susceptibility, 6 , 7 treatment susceptibility, 8 , 9 prognosis prediction, 10 and toxicology 11 of complex diseases in GD mice, demonstrating the advantages of GD mice in terms of simulated genetic diversity.…”
Section: Introductionmentioning
confidence: 99%